A Study of Legal Hermeneutics on the Interpretation of Trademark Law in Commercial Disputes - Putra, I Kadek Ricky Adi; A.A.A Ngr Sri Rahayu Gorda; Kurniawan, I Gede Agus (Faculty of Law, Universitas Pekalongan, 2025)
This study examines the application of legal hermeneutics in interpreting trademark law, particularly within the context of commercial dispute resolution. The legal issue under scrutiny lies in the inconsistency of judicial interpretations of trademark provisions, which often result in legal uncertainty and perceived injustice for business actors. The objective of this research is to analyze how the legal hermeneutic approach can offer a more contextual and equitable understanding in the interpretation of trademark law, especially in light of the evolving dynamics of modern commercial practices. This research employs a normative legal method, incorporating a hermeneutic approach. Data were collected through a literature review of statutory regulations, court decisions, and relevant academic literature. The hermeneutic framework is used to uncover the substantive meaning of legal norms within their social, economic, and cultural contexts. The novelty of this study lies in its application of legal hermeneutics to trademark disputes in Indonesia—an area that has predominantly been analyzed through textual or positivist lenses. The findings indicate that the hermeneutic approach reveals the teleological dimensions and substantive justice values embedded in trademark law interpretation. This method also contributes to producing judicial decisions that are more responsive to the complexities of business relations and consumer protection. The study recommends that judges and legal practitioners begin adopting a hermeneutic legal approach when handling trademark disputes, as a means to enhance legal legitimacy and ensure a more contextually grounded legal certainty